Community Monitoring Interventions to Curb Corruption and Increase Access and Quality in Service Delivery : A Systematic Review - Molina, Ezequiel; Carella, Laura; Pacheco, Ana; Cruces, Guillermo; Gasparini, Leonardo (Taylor and Francis, 2017)
There is a belief that allowing communities monitoring power over providers could be beneficial for improving service delivery and reducing corruption in service delivery. In community monitoring interventions (CMIs), the community is given the opportunity to observe and assess providers’ performance and provide feedback to providers and politicians. This systematic review and meta-analysis appraises and synthesises evidence on the effects of CMIs on access and quality of service delivery and corruption outcomes in low and middle-income countries. The results indicate evidence of beneficial effects of CMIs on service delivery quality and on helping to curb corruption. The potential benefits of CMIs on access to and quality of services are likely to be higher when interventions are designed so that contact between both actors are promoted, and tools for citizens to monitor agents’ performance are provided. However, more rigorous research is needed to address this hypothesis.